LEARNING MATERIAL INTEGRATED ALTERNATIVE TECHNOLOGY IN WASTED ENVIRONMENT OF GOLD MINE TO ENHANCE COGNITION OF ENVIRONMENTAL LITERACY - Novi Nurmayanti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
LEARNING MATERIAL INTEGRATED ALTERNATIVE TECHNOLOGY IN WASTED ENVIRONMENT OF GOLD MINE TO ENHANCE COGNITION OF ENVIRONMENTALMATERI BELAJAR TEKNOLOGI ALTERNATIF TERINTEGRASI DI LINGKUNGAN LIMBAH TAMBANG EMAS UNTUK MENINGKATKAN KEMAMPUAN LINGKUNGANNovi Nurmayanti, Sri AtunUniversitas Negeri Yogyakarta, IndonesiaNovinurmayanti25@gmail.comAbstractWest Kalimantan Province has damages over quater out of its area. It caused by exploration of mining, one of which is gold mining. The decay is needed for responsible of the people, include the students who live arround the area in order to make them qualified in understanding and caring to the environment. The objective of this study is to indicate the cognition improvement of environmental literacy using learning material integrated alternative technology in wasted environment of gold mine. The method used is quasi experiment. Data were collected by doing observation, documentation and test for the experiment class and control class with 31 students for each class. The result showed that there is any of cognition enhancement presented by N-Gain of 0.43 as moderate category in experiment class and 0.13 as low category in control class. The significant improvement of experiment class is attributed by the use of learning material integrated alternative technology in wasted environment of gold mine which is qualified to enhance students’ cognition of environmental literacy.AbstrakProvinsi Kalimantan Barat memiliki kerusakan karena quater keluar dari wilayahnya. Hal itu disebabkan oleh eksplorasi penambangan, salah satunya penambangan emas.Kerusakan ini harus dibertanggung jawabkan oleh masyarakat, termasuk siswa yang tinggal di sekitar daerah agar mereka memenuhi syarat dalam memahami dan peduli terhadap lingkungan. Tujuan dari penelitian ini adalah untuk menunjukkan peningkatan kognisi literasi lingkungan menggunakan bahan pembelajaran teknologi alternatif terintegrasi di lingkungan limbah tambang emas. Metode yang digunakan adalah eksperimen semu. Data dikumpulkan dengan melakukan observasi, dokumentasi dan tes untuk kelas eksperimen dan kelas kontrol dengan 31 siswa untuk setiap kelas. Hasil penelitian menunjukkan bahwa ada peningkatan kognisi yang disajikan oleh N-Gain dari 0,43 sebagai kategori sedang di kelas eksperimen dan 0,13 sebagai kategori rendah di kelas kontrol. Peningkatan yang signifikan dari kelas eksperimen disebabkan oleh penggunaan bahan pembelajaran teknologi alternatif yang terintegrasi dalam lingkungan limbah tambang emas yang memenuhi syarat untuk meningkatkan pengetahuan siswa tentang literasi lingkungan.